On a periodic boundary value problem for second-order linear functional differential equations. (13th November 2005) - Mukhigulashvili, S.
Abstract : Unimprovable efficient sufficient conditions are established for the unique solvability of the periodic problemu ″ ( t ) = ℓ ( u ) ( t ) + q ( t ) for0 ≤ t ≤ ω, u ( i ) ( 0 ) = u ( i ) ( ω ) ( i = 0, 1 ), whereω > 0, ℓ : C ( [ 0, ω ] ) → L ( [ 0, ω ] ) is a linear bounded operator, andq ∈ L ( [ 0, ω ] ) .